Analisis Performa Load Testing Antara Mysql Dan Nosql Mongodb Pada RestAPI Nodejs Menggunakan Postman - Andrianto, Lifan Dwinur; Suyatno, Dwi Fatrianto (Journal of Emerging Information Systems and Business Intelligence (JEISBI), 2024)
With the rapid development of technology, especially in the industrial sector and the widespread use of the internet in Indonesia, effective data storage media is needed. Like MySQL, database management systems (DBMS) have become an effective solution for managing and processing data. As a type of DBMS, MySQL has demonstrated the ability to support application development by both experienced and novice users. On the other hand, in the ever-evolving digital era, web and mobile applications have become important, and Node.js and REST APIs have become the basis for creating effective web applications. Technological advances have also produced an alternative to relationless data storage, known as NoSQL. MongoDB, for example, offers flexibility and fast performance when storing data in JSON document format. Load testing performance analysis between MySQL and MongoDB on Node.js applications is very important because they have different data models and workload types. This is an important technique for measuring and evaluating application performance. Search speed, data storage, and query complexity are influenced by the MySQL and MongoDB NoSQL relational data models. The goal of this load testing performance analysis is to gain an understanding of how MySQL and MongoDB perform when faced with different workloads, particularly in the context of Node.js applications. The results of this analysis are expected to provide a clear picture of the advantages and disadvantages of each database when used with Node.js applications, so that developers and system architects can make wise, data-driven decisions when they use Node.js applications.